The Use of Recycled Polyethylene in Water-Oil Emulsion for Lightweight Concrete - Emmanuel Nangor; Lucas N. W. Damoah; Ebenezer Annan; David Sasu Konadu; Bismark Mensah; Yaw Delali Bensah (International Journal of Polymer Science)
This study was to determine the suitability of recycled waste polyethylene (WPE) processed into water-oil emulsion for lightweight concrete applications. The processed WPE in the form of polyethylene emulsion (PE-e) is to promote physical interaction between the polymeric material and the cementitious matrix. The PE-e used was also to partially replace concrete mix composition by PE-e_1, PE-e_2.5, PE-e_5, and PE-e_10 percents for reference concrete and to introduce plasticity into the mechanical behaviour of the concrete. The PE was processed into PE-e to promote affinity for water, and this hydrophilicity was prominent in PE-e_1 and PE-e_2.5 percent concretes. Concretes with PE-e_1 and PE-e_2.5 percent formed good miscibility with the cementitious matrix. The density of the PE-e concrete decreased to 13.68% with 10% PE-e at 28 days. The replacement of mix constituents of PE-e_1, PE-e_2.5, and PE-e_5 percent induced elastic to plastic behaviour in the concrete coupled with low water absorption. The FTIR data showed characteristic peaks of 3378 cm-1, 1740 cm-1, and 1148 cm-1 in the PE-e. Using optical microscopy, it was shown that the PE particles were homogenously dispersed in the concrete matrix. The study shows the feasibility of using PE-e_1 percent to produce structural lightweight concrete and up to PE-e_10 percent for nonstructural applications mainly for light non-load-bearing partitions.